EFEITOS DE MBTA NO BRIX E ACIDEZ DE TRÃŠS CULTIVARES DE LARANJA - Castro, Paulo R. C.; Alvarez, Ivan A.; Serciloto, Cryz M.; Tavares, Silvio; Kluge, Ricardo A.; Medina, Camilo L.; Jacomino, Angelo P. (REVISTA DE AGRICULTURA, 2015)
EFEITOS DE MBTA NO BRIX E ACIDEZ DE TRÃŠS CULTIVARES DE LARANJA